Integrated Reporting dalam Memoderasi Pengungkapan Emisi Karbon dan Kinerja Lingkungan terhadap Nilai Perusahaan - Pratami, Yolanda; Jamilah, Annisa Wicha Nurul (Akuntansi & Ekonomika, 2025)
This study aims to assess the influence of carbon emission disclosure and environmental performance on firm value, with integrated reporting serving as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The research employs a quantitative approach with a causal design. From a population of 90 companies, 35 were selected as the sample using purposive sampling, yielding 105 panel data observations over three years. Data analysis was conducted using panel regression methods with the EViews 13 software. The findings indicate that carbon emission disclosure has a negative effect on firm value, whereas environmental performance has a positive effect. Furthermore, integrated reporting was found to strengthen the relationship between carbon emission disclosure and firm value, while conversely weakening the relationship between environmental performance and firm value.